2007
DOI: 10.1007/s12028-007-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Prior Statin Use Reduces Mortality in Intracerebral Hemorrhage

Abstract: The significant association of prior statin use with decreased mortality warrants prospective evaluation of the use of statins following ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 40 publications
3
56
1
1
Order By: Relevance
“…18 The potential benefits of statin therapy for human ICH was also described in a recent study in which it was associated with reduced 30-day mortality, but not improved functional outcome. 19 Conflicting results are otherwise found in the literature. The NASIS study showed a reduction of mortality and neurological disability with statin use 20 while FitzMaurice et al failed to reproduce this relationship.…”
Section: Discussionmentioning
confidence: 98%
“…18 The potential benefits of statin therapy for human ICH was also described in a recent study in which it was associated with reduced 30-day mortality, but not improved functional outcome. 19 Conflicting results are otherwise found in the literature. The NASIS study showed a reduction of mortality and neurological disability with statin use 20 while FitzMaurice et al failed to reproduce this relationship.…”
Section: Discussionmentioning
confidence: 98%
“…20,21 A retrospective study found that prior statin use was associated with reduced perihematomal edema and improved survival in a series of patients with nontraumatic intracerebral hemorrhage. 22,23 Analysis of SPARCL data found that statin treatment was associated with an increased risk of hemorrhagic stroke in subjects with prior stroke that was independent of other factors. 1,19 Although limited by small numbers and therefore low statistical power, the current analysis found no difference in the outcomes of hemorrhagic strokes (Figure, bottom panel).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data on statins in ICH is mixed. A small retrospective study of ICH found that pre-stroke statin use was associated with a reduction in mortality 70 and perihematomal DIDs ϭ delayed ischemic deficits; DRS ϭ disability rating score; GOS ϭ Glasgow outcome score; mRS ϭ modified Rankin scale; NIHSS ϭ National Institutes of Health stroke scale; SAH ϭ subarachnoid hemorrhage; TBI ϭ traumatic brain injury.…”
Section: Clinical Experience With Statins For the Treatment Of Acute mentioning
confidence: 99%